2007
DOI: 10.1007/s11547-007-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasonography in the characterization of benign focal liver lesions: activity-based cost analysis

Abstract: This cost analysis shows that CEUS is the least expensive second-line modality after baseline US for the diagnosis of BFLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 14 publications
(6 reference statements)
2
25
0
6
Order By: Relevance
“…Its high capability to show tumoral vascularization makes CEUS accurate in the study of neoangiogenesis and in the follow-up of residual tumor or recurrence after treatment [2][3][4][5][6][7] . The technique is simple, easy and inexpensive compared to CT and MRI, sufficiently noninvasive to be performed on an outpatient basis, and can also be used in patients with renal failure and who are allergic to iodine contrast agents [1,8] . Therefore, CEUS can significantly improve the accuracy of US, leading to improved identification and characterization in the study of pancreatic lesions [2][3][4][5][6][7] .…”
mentioning
confidence: 99%
“…Its high capability to show tumoral vascularization makes CEUS accurate in the study of neoangiogenesis and in the follow-up of residual tumor or recurrence after treatment [2][3][4][5][6][7] . The technique is simple, easy and inexpensive compared to CT and MRI, sufficiently noninvasive to be performed on an outpatient basis, and can also be used in patients with renal failure and who are allergic to iodine contrast agents [1,8] . Therefore, CEUS can significantly improve the accuracy of US, leading to improved identification and characterization in the study of pancreatic lesions [2][3][4][5][6][7] .…”
mentioning
confidence: 99%
“…In a German study of incidentally detected hepatic lesions of uncertain nature [13], CEUS was found to be the most cost-effective approach to diagnosis in outpatients, and was even superior to multiphase CT in this sense. In an Italian decisionmaking model [14], emphasis was placed on the savings associated with CEUS in the diagnosis of benign focal lesions, where it proved to be the least costly of the second-line options. Similar conclusions can be drawn regarding patients with liver disease who have a single, small liver nodule: a prospective study [15] has shown that the extensive use of CEUS after US identification of the nodules can reduce health-care costs.…”
Section: Discussionmentioning
confidence: 99%
“…It is noninvasive and can be accomplished in an outpatient setting. It can also be performed on patients with renal failure or patients allergic to iodine contrast agents [3,15]. Contrary to the contrast agents used in CT or MRI, US contrast agents are generally well tolerated.…”
Section: Introductionmentioning
confidence: 99%